Fiber Weight Fraction Effect to Acoustic Properties of RHDPE Cantula Composite - Muhammad Taufik Burhany Hendrowarsito; Wijang Wisnu Raharjo; Dwi Aries Himawanto (Universitas Sebelas Maret, 2017)
In this study, composites made from recycled HDPE and Cantula fiber have been done and the absorption coefficient have been measured. Composites rHDPE-Cantula were made using hot press for approximately 60 minutes with 170oC temperature while pressure exerted by 50 bar. In this study the weight ratio of Cantula fiber was varied 40%, 50%, 60%, and 70%. Impedance Tube Method was used to measure the sound absorption coefficient in accordance with ASTM E 1050. An increase weight ratio wasn’t influence the sound absorption coefficient significantly, but the optimum sound absorption coefficient shifted to the higher frequencies from 80-200 Hz. An increase weight ratio showed better sound absorption coefficient from 500-1600 Hz, but the result from 60% weight ratio showed low sound absorption coefficient that may caused by it high density leading to the reduction of porosity. This result was supported by density measurement in accordance with ASTM D 792, which the result showed that the sound absorption coefficient increase with decreasing of the density.